PENGARUH KEDALAMAN MUKA AIR TANAH TERHADAP PERTUMBUHAN DAN PRODUKSI SERTA MUTU FISIOLOGIS BENIH KEDELAI (Glycine max (L) Merril) YANG DIHASILKAN - Randika Prasetya; Idwar; Armaini (UIR Press, 2021)
Soybean production in Indonesia has decreased year by year. This is caused by high rainfall potentially causing water-saturated land. This is due to heavy rain which can cause the water to become saturated. Implementation of drainage and groundwater depth control is expected to increase soybean productivity. The purpose of this study is to determine the best groundwater depth for growth, production and physiological quality of soybeans produced. The study was conducted at the Experimental farm of the Faculty of Agriculture, the University of Riau from February to May 2019. The depth of the groundwater used was 5 cm, 10 cm, 15 cm, 20 cm, and control treatment. The parameters observed were plant height and number of nodes, flowering age, age of harvest, number of seeds per plant, dry weight of seeds per plant, the weight of 100 seeds per plant, the suitable percentage for seed, standard germination test, and index value test. Data were analyzed by analysis of variance then continued with Duncan's New Multiple Range Test at the 5% level. The results showed that a depth of 5 cm, which produces poor aeration, leads to unoptimal absorption of nutrients, thus plant height and number of nodes, number of seeds per plant, dry seed weight per plant, 100 seed weight per and the suitable percentage for seed decreased. In the treatment, a water level of 20 cm from the soil gave the best results in terms of seed growth, production and physiological quality due to good ventilation, sufficient water availability and optimal absorption of nutrients.